EFEKTIVITAS LABORATORIUM VIRTUAL SEBAGAI MEDIA PEMBELAJARAN PADA EKSPERIMEN VISKOSITAS - Vebrina Bunga Langngan; Djeli Alvi Tulandi; Theresje Mandang (Charm Sains: Jurnal Pendidikan Fisika, 2021)
Limited laboratory equipment and the current pandemic Covid-19 are the causes of practicum activities not running optimally.to overcome these obstacles, the virtual laboratory can be used as a medium for distance learning. This study aims to determine the effectiveness of using virtttual laboratories as learning media in viscosity experiments. This research is a pre-experimental study with one group pretest-posttest design. The research subjects were semester I Students of the Departement of Physics, Manado State University 2020/2021. Retrieval of data using test instruments in the form of essays and science process skills and affective using rubrics. The average preest results were 43,75 and posttest results were 84,38. The average results of the assessment of science process skills are in good criteria (66%-79%) and very good criteria (80%-100%) while affective assessments are very good criteria (80%-100%). For each student, there were 10 students in high N-Gain category with a percentage of 62,5% and 6 students in the moderate N-Gain category with a percentage of 37,5%. The results of the average N-Gain percentage of 16 students was 74,9%. The results of this study indicate that use of a virtual laboratory is quite effective in being used as a learning medium in viscosity experiments.